JARE ニヨル カイヒョウ モニタリング ニ ムケテ -コクサイ ヒョウジュン ニ モトヅク カンソク テジュン ノ カンリャクカ ト ソノ カツヨウ レイ- - 大島, 慶一郎; オオシマ, ケイイチロウ; 牛尾, 収輝; ウシオ, シュウキ; 大槻, 晃久; オオツキ, アキヒサ; Ohshima, Kay I.; Ushio, Shuki; Otsuki, Akihisa S. (2006)
P(論文) 日本南極地域観測隊(JARE)用の船不海氷目視観測のプロトコルを提案した.ASPeCt(Antarctic Sea ice Processes and Climate)のプロトコルを簡略化したもので,海氷の定量化に必要なものに絞ったものである.このプロトコルに従って,第46次隊から目視観測を開始した.流氷域での観測では,沿岸に近づくにつれて氷厚・変形氷の割合とも大きくなり,海氷の体積が著しく大きくなることが示された.継続した目視観測データの蓄積は,南極沿岸流氷域の海氷(特にその厚さ)の気候値・年々変動を知る不で貴重なものとなる. A protocol for ship-based visual observation of sea ice is proposed for the Japanese Antarctic Research Expedition (JARE). The protocol is a simplified version of the ASPeCt protocol, used for extracting quantitative information on sea ice. The ship-based visual observations started from JARE-46. In the pack ice region, ice thickness, ratio of deformed ice, and total ice volume increased toward the coast. Continuous monitoring of sea ice, particularly its thickness, by ship-based observation is effective for obtaining information on climatology and interannual variation of sea ice in the coastal pack ice region. departmental bulletin paper